Development of the entertainment ethnic animation programs for tourists of different age groups by the example of tourist and ski resort "Migovo" - Скутар, Тетяна; Бойко, Ірина (Чернівецький нац. ун-т, 2017)
The article touches upon the arguments for the need to study and use Ukrainian ethnic and cultural heritage when providing animation services at the regional level. Taking into account the questionnaire results and considering age structure of the respondents, their preferences and subjective assessment of hotel animation, a rough plan of festive events is developed and the minimum required level of their material support is proposed in the publication.
Keywords: animation activity; animation management; animation team; animation tourist services; hotel animation; festive animation programs; Ukrainian festive culture; Ukrainian ethnic and cultural heritage; ethnic animation product